The assisted procreation in the Islamic society. - Atighetchi, Dariusch (Medicina e Morale, 2004)
The absence of the juridical and religious highest authority and of a magistry are the principle factors of several and different interpretations on bioethical issues in the Islamic world. One of the apparently least conflicted issues is the medically assisted procreation. Among Islamic jurists, well-informed on this issues, there are a substantial tolerance with the homologue reproductive technologies and a reject of heterologue ones. The latter are equivalent to an act of adultery, prohibited by the Shari'a. Also the legal adoption is forbidden. The State laws respect these two approaches, both derived from the Shari'a family law. In the article several fatwa of religious authorities on the assisted procreation are analyzed, showing convergences and divergences, and very original reflections of some shi'iti jurists. So it's evident that, among this rich debate, begin to stand out some opinions to support some aspects of the heterologue techniques. The Egyptian case is emblematic to analyze the mentality of population in valuing these new occidental reproductive technologies.